PENENTUAN RUTE DENGAN MEMPERTIMBANGKAN ARMADA KENDARAAN HETEROGEN DAN PRODUK MAJEMUK - Radifan, Nur
PT X is one of the companies operating in the chemical industry. Currently, PT X is still engaged in manual distribution planning activities. This distribution planning involves determining the routes taken by vehicles. The route determination will be addressed using the Vehicle Routing Planning (VRP) method, which can assist in solving this problem. This study will answer how the VRP method can determine vehicle routes by considering heterogeneous vehicle fleets and multiple products. Previous VRP studies with similar characteristics, such as heterogeneous vehicle fleets and multiple products are the research conducted by Ruiz-Meza et al. (2020) and Pollaris et al. (2013). The study by Ruiz-Meza et al. (2020) additionally considers time constraints, while the study by Pollaris et al. (2013) incorporates capacity constraints in terms of tonnage and pallets. Both references will serve as a basis for model development, which will be solved using linear programming with the assistance of the LINGO application. This research presents the results of the VRP model development that aligns with the product distribution conditions of PT X. The model's outcomes demonstrate that the solutions generated by the model can enhance the performance of PT X's distribution activities. Sensitivity analysis of the model also indicates that it is responsive to parameters such as vehicle capacity and demand.